Intrathymic and other anomalous courses of the left brachiocephalic vein in the fetus. (9th September 2016) - Karl, K.; Sinkovskaya, E.; Abuhamad, A.; Chaoui, R.
Abstract: Objective: The left brachiocephalic vein (LBCV), or innominate vein, connects the left jugular vein to the right superior vena cava. Its course is posterior to the thymus and directly anterior and superior to the aortic arch. Pediatric and adult cardiology studies have reported on the subaortic or retrotracheal courses of the LBCV and the presence of double LBCV. We observed recently in the fetus that the LBCV may have a course through the thymus (intrathymic) or be absent in the presence of a left superior vena cava. The aim of this study was to report the prevalence of isolated intrathymic and absent LBCV in normal fetuses undergoing second‐trimester ultrasound screening, as well as the prevalence of other courses in association with cardiac anomalies. Methods: In the prospective part of this study, consecutive second‐trimester ultrasound examinations were evaluated to assess the presence and course of the fetal LBCV. In the retrospective case–control part of this study, the databases of two fetal medicine centers were reviewed for cardiac anomalies and the pattern and prevalence of anomalous courses of the LBCV were reported. Results: One thousand four hundred and eighteen consecutive fetuses were examined prospectively. An intrathymic course of the LBCV with a typical bent shape was found in 1.76% (1 : 57) of cases and the absence of a LBCV in association with a persistent left superior vena cava (LSVC) was found in 0.28% (1 : 350). All fetuses with an isolated intrathymic course or absence of the LBCV had a normal outcome. Over a period of 4.5 years, a total of 1544 fetuses with cardiac malformations were reviewed at two centers. Among these, an anomalous course of the LBCV was noted in eight (0.5%) cases: six subaortic, one retrotracheal and one double LBCV. Conclusion: An intrathymic LBCV is a common condition and appears to be a normal variant in the fetus. The prevalence of a LSVC in our screening population was similar to that reported in previous studies. Anomalous courses of the LBCV are seen occasionally in cases with cardiac malformation. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.